(untitled) (Forum for Linguistic Studies, 2024)
My paper intends to present poesy or poetics or the theory of poetry is nothing but, it is specifically the study of device, structure, form, type and effect with regards to poetry. Poetry evolves from the feeling of poet. Kannada is the language spoken in Karnataka. Karnataka has eight Jnanapith award winners. The highest honour for Indian literature. From the period of adikavi Pampa, who proclaimed his wish to be reborn as a little bee in the land of Kannada. Kannada poetry has come a long way to Kuvempu and Dattatreya Ramachandra Bendre etc.